Inhibitory effects of somatostatin analogue in bleomycin-induced pulmonary fibrosis. (3rd July 2021) - Hosono, Tatsuya; Bando, Masashi; Mizushina, Yoshiko; Sata, Masafumi; Hagiwara, Koichi; Sugiyama, Yukihiko
Abstract: Background and objectives: Idiopathic pulmonary fibrosis (IPF) is a progressive and lethal lung disease. An increased expression of somatostatin receptor subtype 2 in patients with IPF was identified and lung fibroblasts expressed somatostatin receptors in vitro . In addition, somatostatin analogue inhibits the expression of transforming growth factor-β, insulin-like growth factor (IGF) −1, platelet-derived growth factor, and basic fibroblast growth factor. Therefore, we examined the effects of somatostatin analogue on bleomycin-induced pulmonary fibrosis in mice. In a similar model, it has been reported that administration of high-dose somatostatin analogs suppressed acute inflammation and subsequent pulmonary fibrosis. However, it was clarified that the same effect can be obtained even at the dose used in clinical practice. Methods: C57BL/6 mice received a single tracheal instillation of bleomycin. After randomly allocated, mice were treated with subcutaneous injection of either normal saline or somatostatin analogue. Results: Somatostatin analogue reduced the number of neutrophils and lymphocytes in bronchoalveolar lavage (BAL) and IGF-1 level in serum and BAL fluid and attenuated weight loss. The hydroxyproline content of the lung homogenates in somatostatin analogue treatment group was significantly lower than in that of normal saline treatment group. Conclusions: These results suggest that somatostatin analogue may attenuate pulmonary fibrosis after bleomycin treatment at the dose used in clinical practice.